Pathological syndromes of the biliary tract decompression - Rasul T. Mejidov (Eco-vector, 2021)
Background: The increased incidence of cholelithiasis and tumoral lesions of the hepatopancreatoduodenal zone leads to an increase in the number of patients with obstructive cholestasis.